CUSTOMER COST - SECOND IMPORTANT FACTOR FOR IMAGE GAP ANALYSIS OF LIFE INSURANCE SERVICES - BASED ON THE DATA COLLECTION FROM GUWAHATI - Bihani, Pankaj; Bhowal, Amalesh (International Journal of Research -GRANTHAALAYAH, 2016)
The concept of Customer Cost was developed by Lauterborn (1990) while developing the customer oriented Marketing Mix- the 4C concept. 4C model replaces the earlier 4Ps of Marketing Mix, here the focus is on customer and the current chapter is all about the second C of this model i.e. Customer Cost or Price in earlier 4P model. The Customer Cost concept is based on the fact that customers are more concerned with the total cost of acquiring a solution of their problem (Product or Service) rather than the price being charged for the Solution (Product or Service) offered by the Company (Moller, 2006), Customer Cost is a assumed to be a better approach as customers are interested in it. price is the quantity of payment or compensation given by one party to another in return for goods or services. In modern economies, prices are generally expressed in units of some form of currency. (For commodities, they are expressed as currency per unit weight of the commodity, e.g. Rs. per kilogram). Although prices could be quoted as quantities of other goods or services this sort of barter exchange is rarely seen. Prices are sometimes quoted in terms of vouchers such as trading stamps and air miles. In some circumstances, cigarettes have been used as currency, for example in prisons, in times of hyperinflation, and in some places during World War 2. In a black market economy, barter is also relatively common. In many financial transactions, it is customary to quote prices in other ways. The most obvious example is in pricing a loan, when the cost will be expressed as the percentage rate of interest. The total amount of interest payable depends upon credit risk, the loan amount and the period of the loan. Other examples can be found in pricing financial derivatives and other financial assets. For instance the price of inflation-linked government securities in several countries is quoted as the actual price divided by a factor representing inflation since the security was issued. Price sometimes refers to the quantity of payment requested by a seller of goods or services, rather than the eventual payment amount. This requested amount is often called the asking price or selling price, while the actual payment may be called the transaction price or traded price. Likewise, the bid price or buying price is the quantity of payment offered by a buyer of goods or services, although this meaning is more common in asset or financial markets than in consumer markets. Price refers to the amount charged for a product or service (Kotler, 2007), from producer’s point of view Price generates revenue (Kotler, 2003). Whereas Customer Cost concept not only includes the price of the product but also includes other associated costs in addition to the Price of the product or service (Goi, 2009). Customer Cost means the total expenditure a customer is going to spent for purchasing a Customer Solution. Thus Price represents only a part of total cost or Customer’s Cost (Kotler, Armstrong, &haque, 2012).